Rehabilitation of the knee after medial patellofemoral ligament reconstruction - Fithian, D. C.; Powers, C. M.; Khan, N. (Clinics in Sports Medicine, 2010)
The principles of rehabilitation after medial patellofemoral ligament reconstruction are similar to those guiding rehabilitation after other ligamentous reconstructions of the knee, such as anterior cruciate ligament (ACL). The key features are to address pain control, range of motion (ROM), quadriceps strengthening, and proximal lower limb control. Return of full ROM, pain control, and protected weight bearing are stressed in the early phases of recovery. Progression of strength training and return to functional activities follow lines of evidence regarding graft necrosis, remodeling, and tunnel ingrowth, which are most commonly associated with ACL reconstruction.